2022
DOI: 10.1038/s41598-022-21442-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of salt coating of fabrics as a potential antiviral agent in reusable face masks

Abstract: During the coronavirus disease (COVID-19) pandemic, wearing face masks in public spaces became mandatory in most countries. The risk of self-contamination when handling face masks, which was one of the earliest concerns, can be mitigated by adding antiviral coatings to the masks. In the present study, we evaluated the antiviral effectiveness of sodium chloride deposited on a fabric suitable for the manufacturing of reusable cloth masks using techniques adapted to the home environment. We tested eight coating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
(70 reference statements)
2
9
0
Order By: Relevance
“…[24,26] Subsequently, the synthesized polymer was purified by tangential flow filtration (TFF) method with 5 kDa membrane cutoff size. Characterization of LPGS-b-NH 2 by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy (Figures S1-S3, Supporting Information) showed that the ratio between the signals originating from the LPGS-block and covalently linked cysteamine block was as expected for a block copolymer with 155 glycerol and 5 -NH 2 units. Gel permeation chromatography (GPC), using water as mobile phase, (Figure S4, Supporting Information) showed 20 KDa molecular weight for LPGS-b-NH 2 .…”
Section: Synthesis Of Polymersmentioning
confidence: 82%
See 2 more Smart Citations
“…[24,26] Subsequently, the synthesized polymer was purified by tangential flow filtration (TFF) method with 5 kDa membrane cutoff size. Characterization of LPGS-b-NH 2 by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy (Figures S1-S3, Supporting Information) showed that the ratio between the signals originating from the LPGS-block and covalently linked cysteamine block was as expected for a block copolymer with 155 glycerol and 5 -NH 2 units. Gel permeation chromatography (GPC), using water as mobile phase, (Figure S4, Supporting Information) showed 20 KDa molecular weight for LPGS-b-NH 2 .…”
Section: Synthesis Of Polymersmentioning
confidence: 82%
“…Therefore, using antiviral textiles may minimize the secondary transmission of infectious viruses. [13] Moreover, the ability to disinfect and reuse antiviral textiles can significantly reduce environmental pollution. [14] Textiles with antiviral properties are interesting not only in face masks but also in other areas of medicine such as specialty clothing, health care facilities, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we wanted to extend these findings to a material suitable for the manufacture of reusable cloth masks (Konda et al 2020 ; Guha et al 2021 ; Stan et al 2021 ) against the agent of the current COVID-19 pandemic. Three salt-coating conditions (two with spray application and one with dip deposition) were tested and selected on the basis of the results obtained in the same epithelial cell system with influenza A H3N2 virus (Schorderet Weber et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Schorderet Weber et al ( 2022 ) demonstrated that salt coating applied to common textiles suitable for manufacturing of reusable face masks was able to significantly reduce Influenza H3N2 virus replication in an in vitro lung cell culture system. The aim of this work was to verify that reusable face mask made of nonwoven textiles coated with salt were also able to inactivate SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%